PENERAPAN DATA MINING DALAM PROSES PREDIKSI PERCERAIAN MENGGUNAKAN ALGORITMA NAIVE BAYES DI KABUPATEN ACEH TENGAH - Desi Laila Sari; Mahmuda Saputra; Husna Gemasih (Universitas Gajah Putih, 2022)
Marriage in the view of Islam is something sacred, meaning worship to Allah SWT, following the sunnah of the Prophet Muhammad and carried out on the basis of sincerity, responsibility, and following legal provisions that must be heeded. In Aceh province, the divorce rate from Aceh Syari'ah Court data throughout 2017, the number of divorces occurred reaching 5,399. The data and facts about the divorce case are a reality that must be accepted even though it is bitter, and while looking for the best way and strategy to prevent divorce from an early age. Based on the divorce rate which continues to increase every year, it is necessary to have data to determine the factors that influence divorce. Thus, these data can be used as a decision-making tool that can later be a good solution for the government, society and for married couples in the future. Naïve Bayes classification is a simple probability classification based on the application of the Bayes Theorem with the assumption that the explanatory variables are independent or (independent). In this case, it is assumed that the presence or absence of a particular event from a group is not related to the presence or absence and other events. With a system to predict divorce, it can help users who want to know divorce predictions.